Surface Ligands Stabilized Lead Halide Perovskite Quantum Dot Photocatalyst for Visible Light‐Driven Hydrogen Generation. (25th September 2019) - Xiao, Mu; Hao, Mengmeng; Lyu, Miaoqiang; Moore, Evan G.; Zhang, Cheng; Luo, Bin; Hou, Jingwei; Lipton‐Duffin, Josh; Wang, Lianzhou
Abstract: Solar hydrogen conversion represents a clean and economic approach to addressing global energy and environmental issues, for which efficient photocatalysts are heavily pursued. Lead halide perovskites are promising candidates for efficient phtocatalysts in solar hydrogen generation due to their attractive properties in light absorption, photogenerated charge transportation, and utilization. However, photocatalytic applications of lead halide perovskites are limited owing to their poor stability in the presence of water or other polar solvent environment. This work presents the rational control of surface ligands in achieving a good balance between stability and photocatalytic activity of CsPbBr3 quantum dots (QDs). Detailed studies reveal that the deliberate surface ligands engineering is crucial for maximizing the photocatalytic activity of CsPbBr3 QDs while maintaining good QD stability. A certain amount of surface ligands protect the CsPbBr3 QDs from decomposition in moisture during the photocatalytic reaction while still enabling efficient charge transfer for photocatalytic reactions on the surface of QDs. The well‐controlled CsPbBr3 photocatalyst shows efficient visible light‐driven H2 generation with outstanding stability (≥160 h). Abstract : Rational control of surface ligands of lead halide perovskite quantum dots leads to stable and efficient photocatalytic solar hydrogen generation in a gas/solid reaction setup. This concept may provide opportunities for a broad range of metal halide perovskite quantum dots for photocatalytic H2 generation and extend potential applications to the removal of volatile pollutants and air purification.